2016
DOI: 10.1371/journal.pone.0165229
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Irisin Concentration and Serum Cytokines in Mother and Newborn

Abstract: IntroductionIrisin is considered to be a myokine and adipokine that may also participate in reproductive functions, as it increases significantly throughout pregnancy. However, the regulation of circulating irisin and its relationship with other cytokines has not been assessed thus far in pregnant women and their offspring.ObjectiveThe aim of this study was to evaluate differences in irisin and cytokine concentrations between women at the end of pregnancy and their offspring, as well as the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…different ethnic groups and may be influenced by dietary intake however, unlike many adipocyte derived factors, circulating adiponectin levels decrease with increasing adiposity(26,27).On the other hand, irisin concentrations were lower in neonates than mothers, a finding which has been previously observed in pathological conditions, including diabetes and obesity, as well as in uncomplicated pregnancy(28).Differences in neonate and adult muscle mass could explain the increased concentrations of maternal irisin compared to neonatal ones ,in this study. further studies are necessary, this finding may imply that vitamin D metabolites are not correlated with adiponectin irrespective of vitamin D status.…”
supporting
confidence: 62%
“…different ethnic groups and may be influenced by dietary intake however, unlike many adipocyte derived factors, circulating adiponectin levels decrease with increasing adiposity(26,27).On the other hand, irisin concentrations were lower in neonates than mothers, a finding which has been previously observed in pathological conditions, including diabetes and obesity, as well as in uncomplicated pregnancy(28).Differences in neonate and adult muscle mass could explain the increased concentrations of maternal irisin compared to neonatal ones ,in this study. further studies are necessary, this finding may imply that vitamin D metabolites are not correlated with adiponectin irrespective of vitamin D status.…”
supporting
confidence: 62%
“…Using a univariable model, we discovered a positive association between cord blood irisin concentration and PTB occurrence in the studied cohort, that is, a higher irisin level in preterm infants compared with term deliveries. Onset of labor constitutes a strong stimulus for the release of irisin into maternal and fetal circulations [ 44 ] and could increase cord blood irisin level by nearly 40% [ 45 ]. It has been suggested that increased irisin release into cord blood may be caused by temporary utero-placental ischemia during vaginal delivery, thus leading to fetal stress [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma irisin concentration was measured with enzyme-linked immunosorbent assay (ELISA) kit (Phoenix Pharmaceuticals, Burlingame, CA) [ 19 ]. The assay has been proven to be highly sensitive to human irisin.…”
Section: Methodsmentioning
confidence: 99%